Improvement of speed abilities of young tennis players - Mavropulo O.S. ,; Agafonov S.V. ,; Trufanova S.N. ,; Chub S.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to theoretically and practically, we will demonstrate the efficacy of the approach to enhancing the speed capabilities of table tennis players. Methods and structure of the study. The experiment was conducted using the resources of the Rostov-on-Don municipal budgetary institution of additional education «Sports School № 3». Methods and structure of the study. The analysis of literary sources, pedagogical observation, pedagogical testing, pedagogical experiment, methods of mathematical statistics are carried out. The direct participants of the pedagogical experiment were 20 young tennis players aged 9-10 years from the groups of primary training at the sports school (PT 3), 10 of whom were included in the experimental group and 10 players in the control group. Results and conclusions. The outcomes of the trial demonstrated the efficacy of the devised approach in enhancing speed abilities during the educational and training regimen of the tennis players in the experimental group. It was observed that the implementation of specific sets of exercises and game-based activities had a beneficial impact on the performance of all speed-related abilities of the participants in the experimental group, who demonstrated a significant improvement compared to their peers who followed the conventional training program.